Liver fibrosis with two-dimensional shear-wave elastography in patients with autoimmune hepatitis. (2nd July 2020) - Xing, Xian; Yan, Yuling; Shen, Yi; Xue, Mei; Wang, Xiaoze; Luo, Xuefeng; Yang, Li
ABSTRACT: Background: Two-dimensional shear-wave elastography (2D-SWE) is an ultrasound-based real-time 2D-SWE imaging technique for noninvasive assessment of liver fibrosis. The diagnostic performance of 2D-SWE for assessing liver fibrosis in patients with autoimmune hepatitis (AIH) has not been reported. Aims: To evaluate the diagnostic performance of 2D-SWE and serologic tests including the aspartate amino transferase-to-platelet ratio index (APRI) and fibrosis-4 index (FIB-4) for liver fibrosis staging in patients with AIH. Methods: 103 patients were retrospectively collected. Liver fibrosis was staged according to the Scheuer scoring system. The areas under the receiver operating characteristic curves (AUROCs) were used to assess the accuracy of 2D-SWE and serum fibrosis models for staging liver fibrosis. Results: Liver stiffness measured by 2D-SWE had a strong correlation with histological fibrosis stage (r = 0.71, P < 0.0001). The AUROCs of liver stiffness in detecting significant fibrosis, severe fibrosis, and cirrhosis were 0.84, 0.84, and 0.94, respectively. The AUROCs of liver stiffness for detecting significant fibrosis and severe fibrosis were higher than those of APRI (0.57, 0.56) and FIB-4 (0.63, 0.66), respectively. The cut‐off liver stiffness values for predicting significant fibrosis, severe fibrosis, and cirrhosis were 10.0, 15.8, and 19.3 kPa, respectively. Conclusions: 2D-SWE shows promising diagnostic performance for staging liver fibrosis in patients with AIH.